Discutindo a Educação Ambiental em uma escola pública de um reassentamento urbano coletivo de Altamira-PA - OLIVEIRA, Ana Karoline Sousa de (2021)
This paper presents a research classified as qualitative, as its approach, exploratory research, as its objectives, and action research, as its procedures developed in the second semester and 2019 with the objective of: 1 - Know students perceptions and conceptions High School on where they live environmental issues; 2 - Sharpen in these students the critical and reflective thinking about local environmental issues, through the elaboration of a proposal of intervention action on an environmental problem; and 3 - Know obstacles and possibilities for carrying out actions of Environmental Education in the public school of Basic Education. This research aimed at a group of high school students from a public school of a Collective Urban Resettlement on the outskirts of the city of Altamira-PA. For data collection, the following techniques and instruments were used: 1- Questionnaire application; 2 - Chat Wheel; 3 - Preparation of proposition of action plan for intervention on a where they live environmental problem; and 4 - Interview with the school coordination. As a result it was noticed that the reflection provided by the dynamics added critical thinking in the project proposal and dialogues more with an uncritical thinking on Environmental Education themes. In addition, it was realized that the school, the target of this research, needs to develop strategies that aim to improve the perception of its students around the environmental problems present there.